Development of indirect enzyme-linked immunosorbent assay for detection of porcine epidemic diarrhea virus specific antibodies (IgG) in serum of naturally infected pigs - Myint, Ohnmar; Yoshida, Ayako; Sekiguchi, Satoshi; Van Diep, Nguyen; Fuke, Naoyuki; Izzati, Uda Zahli; Hirai, Takuya; Yamaguchi, Ryoji (BMC veterinary research, 2019)
Background Porcine epidemic diarrhea virus (PEDV) infection is a highly contagious infectious disease causing watery diarrhea, vomiting, dehydration and high mortality rate in newborn piglets. PEDV infection can cause high economic losses in pig industry. In Japan, a PEDV outbreak occurred with high mortality from 2013 to 2015. Even though until now, PEDV infection occurs sporadically. For the control and monitoring of PEDV infection, not only symptomatic pigs, but also asymptomatic pigs should be identified. The objective of this study is to develop and optimize novel indirect ELISA as a simple, rapid, sensitive and specific method for the detection of anti-PEDV antibodies and evaluate the efficacy of the assay as a diagnostic method for PED. Results One hundred sixty-two serum samples, consisting of 81 neutralization test (NT) positive and 81 NT negative sera, were applied to the assay. Indirect ELISA test based on whole virus antigen (NK94P6 strain) derived from Vero cell culture was evaluated by receiver operating characteristic (ROC) analysis with neutralization test (NT) as a reference method, and cut-off value was determined as 0.320 with sensitivity and specificity of 92.6 and 90.1%, respectively. The area under curve (AUC) was 0.949, indicating excellent accuracy of indirect ELISA test. There was significant positive correlation between indirect ELISA and neutralization test ( R = 0.815, P < 0.05). Furthermore, the kappa statics showed the excellent agreement between these two tests (kappa value = 0.815). In addition, the sensitivity and specificity of preserved plates with different periods (1 day, 2 weeks, 1, 2, 3, 4, 5 and 6 months) after drying antigen coated plates were 100% and 80–100%, respectively. Conclusions The developed indirect ELISA test in our study would be useful as a reliable test for serological survey and disease control of PEDV infection, and our pre-antigen coated ELISA plates can be preserved at 4 °C until at least 6 months.